Development of a Web-Based 360-Degree Virtual Tour for AEWO Mulyaharja Tourism Village Using the MDLC - Fami, Amata; Nasir, Muhammad; Renanti, Medhanita Dewi; Wicaksono, Aditya; Aziezah, Nur; Barus, Irma R.G.; Indriasari, Sofiyanti (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Digital tourism increasingly requires interactive and immersive media, yet virtual tour development in rural and community-based settings often lacks methodological rigor, structured usability evaluation, and user-centered design. To address this gap, this study develops a web-based 360-degree Virtual Tour for AEWO Mulyaharja using the Multimedia Development Life Cycle (MDLC) framework. Introductory Augmented Reality (AR) elements were included to enrich visual presentation, although these features were not the primary focus of evaluation. The system was developed through the six MDLC stages and assessed using an adapted usability instrument derived from the principles of the System Usability Scale (SUS), simplified to accommodate respondents with varying levels of digital literacy. Thirty participants tested the system and rated five aspects: attractiveness, ease of use, information completeness, intention to visit, and cross-device accessibility. The Virtual Tour achieved an average usability score of 81.68 percent, categorized as “very good,” indicating that the platform is engaging, clear, and accessible for potential users. Scientifically, the study contributes to digital tourism literature by integrating MDLC with Human–Computer Interaction considerations and demonstrating the contextual application of an adapted usability measure for community-based environments. Practically, the Virtual Tour enhances AEWO Mulyaharja’s digital visibility and offers a replicable model for rural tourism digitalization. Future research may explore deeper evaluation of AR functionality, broader respondent groups, and additional usability metrics